Effect of PQT-12 interface layer on the performance of PCDTBT: PCBM bulk heterojunction solar cells. (4th October 2019) - Kumar, Amit; Ratan, Smrity; Jarwal, Deepak Kumar; Mishra, Ashwini Kumar; Kumar, Chandan; Singh, Abhinav Pratap; Mukherjee, Bratindranath; Jit, Satyabrata
Abstract: The effect of PQT-12 interface layer on the performance of PCDTBT:PCBM based bulk heterojunction (BHJ) organic solar cells (OSCs) is reported in this paper. The PQT-12 interface layer is obtained by cost and material effective technique, floating film transfer method (FTM). It is shown that the use of FTM-based PQT-12 HTL significant improves the power conversion efficiency (PCE) and external quantum efficiency (EQE) of the OSCs over only PEDOT:PSS HTL based OSCs. The OSC has the maximum values of JSC (=5.62 mA cm −2 ), VOC (=562 mV) and FF (=0.33) in the PQT-12 incorporated structure due to efficient carrier transfer at the interface. The PCE of nearly twice of the only PEDOT:PSS HTL OSC is obtained in case of the PQT-12/PEDOT:PSS structure.